The Effects Of Leadership, And Organizational Culture Career Development To Work Satisfaction Employees At PT SPV, Purwakarta West Java - Sihite, Otto Berman; Sulistiadi, Andi; Utama, Virza (2020)
The author makes the purpose of the research is to know the Human Resource Governance that occurred at PT SPV, Purwakarta West Java by examining the influenceaofaLeadership, OrganizationalaCultureaand Career Development on Job Satisfaction. Another reason of this reseach is due to high turn over of the employee during 5 years. The research sample is taken from Senior Employee at a company as much as 265 people but by using a sampling technique to 90 employees at PT SPV Purwakarta, West Java selected by proportional random sampling method. Data were collected using questionnaires and analyzed using SPSS 20.00. The results showed that Leadership is a very significant effect on Employee Job Satisfaction, Organizational Culture Influence on Job Satisfaction, and career development have a significant effect on Job Satisfaction. The implications of this research are to improve the elements Leadership and working relationships in order to promote temporary career development. The elements of career development are essential to showing job satisfaction. The result will see the effect of this research toward the high turn over in coming years. The result of this research proved that the Leadership and and Career development are the one to be improved or to develop as they are significantly effected to the work satisfaction in the company. This actions will help company to reduce the employee turnover.